Measuring Productivity using the Index Number Approach: An Introduction - Nathan McLellan (New Zealand Government, The Treasury, 2004)
This paper provides an introduction to productivity measurement using index number techniques. Attention is given to the construction of productivity series using common index number formulae, the economic and axiomatic approaches to selecting an index number formula, and the use of chaining. Special attention is also given to measuring physical capital inputs and quality adjusted labour inputs. Numerical examples are used throughout the paper to illustrate the analysis.
Keywords: C43; D24; E23; 330; Productivity measurement; index numbers; capital; quality-adjusted labour inputs